Economically viable synthesis of Fe3O4 nanoparticles and their characterization - Srivastava V.; Singh P.; Weng C.; Sharma Y. (My University, 2025)
Nano iron oxide particles (Fe3O4) were synthesized by coprecipitation of Fe2+ and Fe3+ by ammonia solution in the aqueous phase. Various instrumentation methods such as X ray Diffractometry (XRD), Transmission Electron Microscopy (TEM), Fourier Transform Infrared (FTIR) spectroscopy, Brunauer-Emmett-Teller (BET) and Vibrating Sample Magnetometery (VSM) were used to characterize the properties of nanoparticles. The size of the nanoparticles was measured and was found to be between 10 to 15 nm. The value of saturation magnetization of the nanoparticles was found to be 55.26 emu/g. The BET surface area of nano iron oxide particles measured to be 86.55 m 2/g.